Association Between Shift Work, Sleepiness, Chronic Fatigue, and Incident Occurrence in Nurses: A Generalized Structural Equation Modeling Approach - Mehrzad Ebrahemzadih; Gholam Hossein Halvani; Sara Jam Barsang; Sahar Khodi (Sleep Medicine Research)
Background and Objective This study aimed to determine the association between shift work, sleepiness, chronic fatigue, and incident occurrence among educational hospital nurses. Methods This cross-sectional study was carried out in the educational hospital in Yazd–Iran. Using a stratified sampling technique 200 nurses were selected, comprising 100 shift-working nurses and 100 non-shift-working nurses from various departments of the educational hospitals. Demographic information, sleepiness (Epworth Sleepiness Scale), and chronic fatigue (Chalder Fatigue Scale) were assessed via questionnaires. A checklist was used to determine the incident type, cause, location, and frequency in the past 12 months. All statistical analyses, including the development and integration of the structural equation model, were performed using STATA software version 13. Results The results demonstrated a statistically significant association between shift work and incident occurrence (p-value>0.001). The results of this study indicate that the chance of incidents occurring in shift-working nurses is approximately 3.6 times higher than in nurses who do not work shifts. A significant majority of nurses (86.7%) who experienced incidents showed signs of chronic fatigue syndrome and sleepiness. Conclusions The findings suggest that nurses in two-shift systems experience advantages such as better recovery between shifts and higher quality of life. This study provides insights to enhance nurses’ well-being, patient safety, and quality of care.